Percutaneous Transfistulous Interventions for Intractable Pancreatic Fistula - Masahiko Hirota (Radiology Research and Practice)
Three techniques for the treatment of intractable pancreatic fistula: percutaneous transfistulous pancreatic duct drainage (PTPD), percutaneous transfistulous pancreatojejunostomy (PTPJ), and percutaneous transfistulous pancreatic duct embolization (PTPE) are presented as treatment options for intractable pancreatic fistula. PTPD is effective for most cases of intractable fistula that communicate with the main pancreatic duct. However, PTPD itself is not enough in some specific cases. PTPJ and PTPE are applicable in such cases.